2009
DOI: 10.1002/ppul.21028
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between antimicrobial proteins and airway inflammation and infection in cystic fibrosis

Abstract: Antimicrobial proteins are important in lung defense and are potential therapeutic agents in chronic airways infection such as seen in cystic fibrosis (CF). In preparation for future clinical studies, we sought (1) to determine levels of three antimicrobial proteins [lactoferrin, lysozyme, and secretory leukoprotease inhibitor (SLPI)] in the CF airway and (2) to examine the relationships between these antimicrobial proteins and airway inflammation and infection. We examined bronchoalveolar lavage fluid (BALF) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 42 publications
2
52
0
Order By: Relevance
“…There was also a trend of higher BALF protein levels in mice that inhaled 5 and 25% DE than inhalation of PBS, although these values did not reach formal significance (p<0.05). Measurement of BALF components including immune cells, microbial/host protein content, cytokines and chemokines, is the method of choice for elevating airway and lung inflammation (Elizur et al, 2008;Sagel et al, 2009). This is consistent with findings reported by Poole et al (2007) where acute exposure to dust induces an inflammatory response demonstrated by secretion of proinflammatory cytokines; however, re-stimulation resulted in a diminished response.…”
Section: Discussionsupporting
confidence: 80%
“…There was also a trend of higher BALF protein levels in mice that inhaled 5 and 25% DE than inhalation of PBS, although these values did not reach formal significance (p<0.05). Measurement of BALF components including immune cells, microbial/host protein content, cytokines and chemokines, is the method of choice for elevating airway and lung inflammation (Elizur et al, 2008;Sagel et al, 2009). This is consistent with findings reported by Poole et al (2007) where acute exposure to dust induces an inflammatory response demonstrated by secretion of proinflammatory cytokines; however, re-stimulation resulted in a diminished response.…”
Section: Discussionsupporting
confidence: 80%
“…[27][28][29] In addition, airway epithelial cells produce several other major host defense molecules such as lactotransferrin. 30 The present results of impaired Mp clearance from SPLUNC1 Ϫ/Ϫ mouse lungs advance the lung innate immunity field by demonstrating the in vivo function of SPLUNC1. Furthermore, it was demonstrated that hSPLUNC1 inhibited Mp growth, thus extending previous results using mouse SPLUNC1 protein.…”
Section: Discussionmentioning
confidence: 93%
“…Instead, P. aeruginosa growth in the CF airway occurs in the context of stagnant mucous plugs, which are lodged in the airway lumen (6,11). The exuberance of the immune response results in excessive neutrophil accumulation that can overwhelm the capacity of the host to clear neutrophils from the tissue, resulting in sputum that is highly enriched in neutrophil-derived products implicated in CF lung pathogenesis (1,(14)(15)(16)(17)(18)(19). Neutrophil survival in this setting is limited to just a few hours as a consequence of apoptosis and necrosis (20,21).…”
mentioning
confidence: 99%